Interleukin-1 Receptor Antagonist Modulates Inflammation and Scarring after Ligament Injury - Chamberlain, Connie S. (2014)
Ligaments have limited regenerative potential and as a consequence, repair is protracted and results in a mechanically inferior tissue more scar-like than native ligament. We previously reported that a single injection of interleukin-1 receptor antagonist (IL-1Ra) delivered at the time of injury, decreased the number of M2 macrophage-associated inflammatory cytokines. Based on these results, we hypothesized that IL-1Ra administered after injury and closer to peak inflammation (as would occur clinically), would more effectively decrease inflammation and thereby improve healing. Since IL-1Ra has a short half-life, we also investigated the effect of multiple injections. The objective of this study was to elucidate healing of a medial collateral ligament (MCL) with either a single IL-1Ra injection delivered one day after injury or with multiple injections of IL-1Ra on days 1, 2, 3, and 4. One day after MCL injury, rats received either single or multiple injections of IL-1Ra or PBS. Tissue was then collected at days 5 and 11. Both single and multiple IL-1Ra injections reduced inflammatory cytokines, but did not change mechanical behavior. A single injection of IL-1Ra also reduced the number of myofibroblasts and increased type I procollagen. Multiple IL-1Ra doses provided no additive response and, in fact, reduced the M2 macrophages. Based on these results, a single dose of IL-1Ra was better at reducing the MCL-derived inflammatory cytokines compared to multiple injections. The changes in type I procollagen and myofibroblasts further suggest a single injection of IL-1Ra enhanced repair of the ligament but not sufficiently to improve functional behavior.